Tanzania : Financial Sector Assessment - World Bank (Washington, DC, 2013)
This Financial Sector Assessment summarizes the findings of the joint World Bank-International Monetary Fund (IMF) financial sector assessment program (FSAP). The overall assessment of development priorities, and financial stability suggest that even though the current depth, and efficiency of Tanzania's financial system fall well short of what is needed to help support economic growth, there are clear indications that the foundations of a sustainable advance are being laid. Extensive policy reforms have been put in place, notably the organizational, and financial restructuring of the two largest banks, the opening of entry to financial services providers, and the substantial liberalization of domestic financial intermediation. But these sweeping reforms did not at first yield improved access to financial services by economic agents. There has been however, an accelerated pick-up in credit in the last two years, with an intensified competition for creditworthy borrowers at all levels in the urban areas. Yet, large swathes of the economy are, however, working with little formal credit. This is true of much of agriculture, and the rural economy, thus new business models and lending technologies, need to be bought into play. A key task for government will be to help ensure the legal, and information infrastructures on which the banks, and other financial institutions can build. Two competing visions of Tanzania's future financial sector differ as to whether micro, and small-scale financial services will be provided more by formal sector banks reaching down, or by the development of community - or nongovernmental (NGO)-based micro-finance institutions (MFIs). Main elements for the development of the Tanzanian financial system, and its institutional, and financial strengthening requires a long-term, planned approach, that includes reform of government-owned financial institutions; legal and judicial reform; enhanced access to financial services; long-term investment, by liberalizing investment requirements for insurance companies; managing systemic liquidity, market intervention, and infrastructure, and, immediate reviewing of some regulations as mentioned, aimed at relaxing unduly constraining barriers; and, the development of a financial system crisis prevention and management plan, and tax reform.